Dysbiosis of the Duodenal Mucosal Microbiota Is Associated With Increased Small Intestinal Permeability in Chronic Liver Disease. Issue 8 (August 2019) - Raj, Ashok S.; Shanahan, Erin R.; Tran, Cuong D.; Bhat, Purnima; Fletcher, Linda M.; Vesey, David A.; Morrison, Mark; Holtmann, Gerald; Macdonald, Graeme A.
Abstract : OBJECTIVES: Chronic liver disease (CLD) is associated with both alterations of the stool microbiota and increased small intestinal permeability. However, little is known about the role of the small intestinal mucosa-associated microbiota (MAM) in CLD. The aim of this study was to evaluate the relationship between the duodenal MAM and both small intestinal permeability and liver disease severity in CLD. METHODS: Subjects with CLD and a disease-free control group undergoing routine endoscopy underwent duodenal biopsy to assess duodenal MAM by 16S rRNA gene sequencing. Small intestinal permeability was assessed by a dual sugar (lactulose: rhamnose) assay. Other assessments included transient elastography, endotoxemia, serum markers of hepatic inflammation, dietary intake, and anthropometric measurements. RESULTS: Forty-six subjects (35 with CLD and 11 controls) were assessed. In subjects with CLD, the composition ( P = 0.02) and diversity ( P < 0.01) of the duodenal MAM differed to controls. Constrained multivariate analysis and linear discriminate effect size showed this was due to Streptococcus-affiliated lineages. Small intestinal permeability was significantly higher in CLD subjects compared to controls. In CLD, there were inverse correlations between microbial diversity and both increased small intestinal permeability ( r = −0.41, P = 0.02) and serum alanine aminotransferase ( r = −0.35, P = 0.04). Hepatic stiffness was not associated with the MAM. DISCUSSION: In CLD, there is dysbiosis of the duodenal MAM and an inverse correlation between microbial diversity and small intestinal permeability. TRANSLATIONAL IMPACT: Strategies to ameliorate duodenal MAM dysbiosis may ameliorate intestinal barrier dysfunction and liver injury in CLD.